Striving toward quality metrics for pediatric stroke: time from door to diagnosis - Pearson, Rachel; Hills, Nancy K.; Bacon, Kellie; Shelton, Shelby K.; Roque, Rowena; Moreno, Tatiana; Kuchherzki, Maria; Schultz, Carl; Heyming, Theodore W.; Fox, Christine K.; Fullerton, Heather J. (Frontiers in Stroke, 2026)
Background/ObjectiveMost pediatric stroke survivors suffer long-term impairments. To minimize injury, it is essential to quickly restore perfusion to viable brain tissue. Minimizing the time to stroke diagnosis requires recognition of a possible stroke by prehospital and emergency healthcare personnel, and rapid neuroimaging. While CT suffices for diagnosing hemorrhagic stroke, MRI is necessary to diagnose acute ischemic stroke (IS), contributing to significant diagnostic delays and potentially missed opportunities for intervention.MethodsWe conducted a retrospective study of children 1–14 years old with acute neurological symptoms presenting by Emergency Medical Services (EMS) to the study institution from 1/2019–6/2023. We described patient characteristics and neuroimaging studies, then evaluated predictors of MRI acquisition and actionable findings, including stroke. To assess the generalizability of these data we analyzed a secondary retrospective cohort of all children admitted during this period with out-of-hospital strokes regardless of presentation modality [EMS, emergency department (ED) walk-in, and transfer].ResultsAmong 3,888 pediatric patients with acute neurological symptoms presenting via EMS, 695 (17.9%) had neuroimaging: CT only in 570 patients (14.7%); CT and MRI in 125 (3.2%). Median (IQR) times from EMS activation to neuroimaging were 2.29 (1.56, 3.21) hours for CT and 26.8 (16.3, 43.8) hours for MRI. An EMS primary impression of “stroke” was rare (n = 13) but strongly predictive of imaging acquisition: all had CT and 11 had MRI. Thirty-one of the 125 patients with MRI had actionable MRIs, including nine acute strokes. During the study period another 14 stroke patients presented as ED walk-ins. Median time from ED arrival to CT was 0.92 (0.47, 1.08) hours for EMS patients with hemorrhagic stroke and 5.69 (1.50, 9.76) hours for walk-ins; for MRI, median time was 4.15 (3.00, 5.31) hours for EMS patients with ischemic stroke and 10.2 (1.99, 36.3) hours for walk-ins.ConclusionAmong children with acute neurological symptoms selected for neuroimaging, CT was the most common modality while MRIs were performed with a substantial time delay. While EMS providers rarely suspected stroke, their diagnosis impacted imaging decisions in the ED, suggesting a need to raise awareness among prehospital providers. To measure quality improvement in pediatric stroke, new pediatric-specific metrics like “door to diagnosis” time, should be further explored.